Development of a Recombinase Polymerase Amplification Assay for Schistosomiasis Japonica Diagnosis in the Experimental Mice and Domestic Goats - Guo, Qinghong; Zhou, Kerou; Chen, Cheng; Yue, Yongcheng; Shang, Zheng; Zhou, Keke; Fu, Zhiqiang; Liu, Jinming; Lin, Jiaojiao; Xia, Chenyang; Tang, Wenqiang; Cong, Xiaonan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Although the prevalence of Schistosoma japonicum (S. japonicum) has declined gradually in China, more accurate and sensitive diagnostic methods are urgently needed for the prevention and control of this disease. Molecular diagnostic methods are advantageous in terms of sensitivity and specificity, but they are time-consuming and require expensive instruments and skilled personnel, which limits their application in low resource setting. In this study, an isothermal DNA amplification assay, recombinase polymerase amplification (RPA) combined with lateral flow dipstick (LFD) was set up, and it was used to detect S. japonicum infections in experimental mice and domestic goats by amplifying a specific DNA fragment of S. japonicum. The lower limit of detection the LFD-RPA assay was evaluated using dilutions of plasmid containing the target sequence. Cross-reactivity was evaluated using genomic DNA from eight other parasites. The effectiveness of the LFD-RPA assay was verified by assessing 36 positive plasma samples and 36 negative plasma samples from mice. The LFD-RPA assay and real-time PCR were also used to assess 48 schistosomiasis japonica positive plasma samples and 53 negative plasma samples from goats. The LFD-RPA assay could detect 2.6 fg of S. japonicum target DNA (~39 fg genomic DNA of S. japonicum), only 10-fold less sensitive than real-time PCR assay. There was no cross-reactivity with DNA from the other eight parasites. The whole amplification process could be completed within 15 min at 39°C, and the results can be observed easily using the LFD. The sensitivity and specificity of the LFD-RPA assay were 97.22% (35/36, 95% CI, 85.47–99.93%) and 100% (36/36, 95% CI, 90.26–100%) in mice, and 93.75% (45/48, 95% CI, 82.80–98.69%) and 100% (53/53, 95% CI, 93.28–100%) in goats. By comparison, the sensitivity and specificity of real-time PCR were 100% (36/36, 95% CI, 90.26–100%) and 100% (36/36, 95% CI, 90.26–100%) for mice, and 97.92% (47/48, 95% CI, 88.93–99.95%) and 100% (53/53, 95% CI, 93.28–100%) for goats. The LFD-RPA assay exhibits high sensitivity and specificity for the diagnosis of schistosomiasis japonica, and it is an alternative method for diagnosis schistosomiasis japonica in low resource setting.